Biogerontology - Rattan, Suresh I. S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Biogerontology has now developed a solid scientific base with respect to the understanding of the phenomenon of aging. A spectrum of new and innovative strategies and approaches are being increasingly applied to modulate the process of aging at the level of cells, tissues, organs and organisms. Biogerontology represents this step in research which aims primarily at achieving healthy old age accompanied by improved longevity. The focus is on attempts to understand, prevent, cure or minimize age-related impairments. The science of healthy old age requires its own platform to bring forward new ideas, and to encourage the scientific publication of innovative and bold experimental manipulations in this regard. Biogerontology therefore provides a peer-reviewed forum for publishing original research data, new ideas and discussions about: Modulating the aging process by physical, chemical and biological means, including transgenic and knockout organisms; Cell culture systems to develop new approaches and health care products for maintaining and/or recovering the lost biochemical functions; Immunology, autoimmunity and infection in aging; Vertebrates, invertebrates, micro-organisms and plants for experimental studies on genetic determinants of aging and longevity; Biodemography and theoretical models linking aging and survival kinetics. Biogerontology will publish: original research reports; reviews, hypotheses, new methods and interviews; special issues on specific topics relating to aging, health and longevity.
Keywords: Geriatrics; Cell biology; Developmental biology; Cell Biology; Geriatrics/Gerontology.; Developmental Biology